No place like home: Patriotism and femininity in German reality television. (March 2018) - Graefer, Anne
In the current recession, German television has developed a particular proclivity for 'emigration shows'. In this article, I explore the most prominent of these, Goodbye Deutschland – Die Auswanderer ( Goodbye Germany – The Emigrants, since 2006). Through a figurative analysis, I investigate how Goodbye Germany produces its female protagonists as failed national subjects worthy of social derision and contempt. By highlighting how the programme equates the departure from Germany with a departure from coherent feminine respectability, I show how we can understand this programme as a cultural expression of 'commercial nationalism' that produces Germany as a 'safe haven' within an economically unstable Europe.